NATIONAL SPORTS GAMES IN THE NEIGHBORHOOD THE IMPORTANCE OF ESTABLISHMENT - A.Mukhidinov; Sh.Tillaev (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
One of the most pressing issues on the agenda is the issue of educating young people physically healthy through the effective organization of national sports games in the neighborhoods. In order to fulfill this important and priority task at the required level, there is a need to study the socio-psychological aspects of this issue.